Menyulut Energi Positif: Bagaimana Konflik yang Dikelola dengan Baik Memperkuat Kohesivitas Kelompok pada Generasi Z - Wahyunita Euniche Elizabeth Loe; Patriana Minandra Boboy; Joel Mellu; Afrona Elisabeth Lelan Takaeb; Christina Rony Nayoan (Yayasan Literasi Sains Indonesia, 2025)
Conflict is an unavoidable aspect of group dynamics, including among Generation Z, who are known for their familiarity with digital technology and their inclination towards communication and dialogue. Conflict has the potential to either strengthen or fracture a group. This article explores how effective conflict management can enhance group cohesion within Gen Z. We identify common causes of conflict, such as differences in opinion, misunderstandings, and heightened sensitivity. Various conflict management strategies are analyzed in depth. These include identification, assessment, and problem-solving (Fisher et al.), or avoidance, escalation, and maintenance strategies (Frost and Wilmot). Other approaches like deciding conflict (through domination, compromise, or integral problem-solving), stimulating conflict, reducing conflict, avoiding conflict, and accommodation are also presented as flexible frameworks. Given Gen Z's comfort with multi-personal interactions and discussions, strategies promoting consensus-building, constructive confrontation, and the achievement of shared goals will be highly effective. With proper management, conflict can be transformed into positive energy, fostering sustainable shared experiences, nurturing group bonds and pride, and ultimately significantly strengthening the unity and identity of Generation Z.